Global, regional, and national trends and burden of multiple sclerosis in adolescents and young adults: a data analysis from 1990 to 2021 and projections to 2040 - Zhao, Peixi; Guan, Chang; Lu, Jing; Zhang, Ying; Wang, Baitong; Huang, Lin; Ye, Ding; Nan, Hongmei; Wang, Jian; Xu, Peng (Frontiers in Immunology, 2025)
Background and ObjectivesMultiple sclerosis (MS) significantly impacts adolescents and young adults (aged 15–39 years), causing substantial neurological disability. Despite therapeutic advances, the global burden persists due to disparities in healthcare access and lifestyle factors. This study analyzes global, regional, and national trends and burdens of MS using Global Burden of Disease (GBD) 2021 data, emphasizing the influence of the Socio-demographic Index (SDI).MethodsUsing data from the GBD 2021 data, we conducted a secondary analysis. We assessed the prevalence, mortality, and disability-adjusted life years (DALYs) of MS across 204 countries/territories from 1990 to 2021, calculating age-standardized rates.ResultsIn 2021, global MS prevalence was 489,310 cases, associated with 1,424 deaths and 215,869 disability-adjusted life years (DALYs). The global age-standardized rates per 100,000 were: prevalence 22.2 (19.8 - 24.8), deaths 0.2 (0.2 - 0.2), and DALYs 11.4 (9.8 - 13.2). Compared to 1990, these rates decreased by 0.4%, 12.8%, and 11.0% respectively, while the number of prevalent cases increased by 52.4%. Sweden (161.6), Canada (134.2), and Norway (131.5) had the highest age-standardized prevalence. The UK (71.3) had the highest and Nauru (0.4) the lowest age-standardized DALY rate. Female MS death rates exceeded those of males across all ages, peaking at 20–24 years. Regionally, age-standardized DALY rates showed an inverse V-shaped relationship with the SDI.DiscussionAlthough the global MS burden among adolescents and young adults (AYAs) decreased, the substantial and rising prevalence demands attention. The burden from premature mortality and stark geographic variations in prevalence and DALYs indicate inadequate disease management, underscoring the need for enhanced awareness and effective interventions. Urgent, targeted healthcare policies are required to address geographical inequities, sex-specific pathophysiology, and modifiable risk factors such as smoking.